Persistent symptoms in mild pediatric traumatic brain injury - Chendrasekhar, Akella (Pediatric Health Med Ther, 2019)
Background: Traumatic brain injury (TBI) is the leading cause of morbidity and mortality for children in the US. The objective was to examine the epidemiology of self-reported neurologic and neuro-psychiatric symptoms in pediatric patients with mild TBI within 14 months post-injury. Methods: A telephone based survey was conducted on all pediatric patients (aged<15 years) with a mild traumatic brain injury diagnosed at our urban level 1 adult/level 2 pediatric trauma center within 1 year. Subjects were identified by our trauma registry, and medical records were reviewed for demographic data and mechanism of injury. Parents or guardians were interviewed using a standardized questionnaire to collect data regarding the presence or absence of headaches, weakness, numbness, coordination impairment, speech impairment, nausea, vomiting, confusion, short-term memory impairment, sleep disturbances, anhedonia, depression, anxiety, fear, and agitation. Results: Thirty-three parents of patients responded. The average age of the patients at time of TBI was 9.3±1.7 years. The age range was 3–14 years. The mechanisms of injury included pedestrian struck (54.5%), fall (39.4%), motor vehicle collision (3%), and assault (3%). The time from injury was stratified into 1–3 months (n=9), 4–6 months (n=9), 7–9 months (n=6), and 10–12 months (n=8), one patient surveyed was 14 months post-injury. Headaches (39.4%), anxiety (30.3%), fear (18.2%), and anhedonia (18.2%) were the most frequently reported symptoms. Less common were sleep disturbances (12.1%), depression (9.1%), nausea (6.1%), coordination impairment (6.1%), short-term memory impairment (6.1%), weakness (3%), numbness (3%), vomiting (3%), and agitation (3%). There were no instances of speech impairment. Conclusions: Approximately 1/3 of patients complained of anxiety post-injury, and 1/5 reportedly experienced anhedonia and fear. Considering the ongoing neurologic and psychosocial development of the pediatric population, long-term follow-up and periodic screening examinations should be considered in patients diagnosed with TBI.